FLUORESCENT LAMP LIGHT INTENSITY ON THE EMBRYOGENESIS DEVELOPMENT AND THE SURVIVAL OF PEARL OYSTER (Pinctada maxima) LARVAE - Mat Sardi Hamzah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
One of the important factors in determining the success of pearl oyster (Pinctada maxima) culture is the quality and quantity of larvae produced in brood stock spawning process in the laboratory. Problems were often found in larval rearing and larvae attachment to the substrate that were low in quality and little number of larvae. The study purposes were observe the embryogenesis development and the survival rate of pearl oyster larvae under different fluorescent lamp light intensities. The study was conducted in August 1nd – 30th, 2011 in Sambelia Bumi Gemilang Hamparan Mutiara laboratory, East Lombok. Results revealed that different in light intensities effected the survivorship of the pearl oyster larvae significantly (p<0.01). Honest Significant Difference (HSD) test indicated that the highest survival rate occurred in dark condition (dark treatment) of 38%, followed by intensity of 10 watts (34.67%), 5 watts (30.67%) and 15 watts (4.66%) resfectively Keywords: embryogenesis development, survivorship, pearl oyster (Pinctada maxima) larvae,  fluorescent lamp light intensity